Soy product consumption and the risk of major depressive disorder in older adults: Evidence from a cohort study - Zhang, Tao; Jiang, Guojun; Li, Fudong; Gu, Xue; Zhai, Yujia; Xu, Le; Wu, Mengna; Shen, Hongwei; Lin, Junfen (Frontiers in Psychiatry, 2022)
Background To explore the association between soy product consumption and the risk of depression in the community. Methods In 2014, a total of 10,901 older people were recruited from Zhejiang province, China, and completed food frequency interviews. Participants were followed up over the next 6 years, and depression was assessed at each visit. Finally, 6,253 participants were included in the present study. Mixed effects models were performed to analyze the association by multivariate adjustments for potential confounders. Results Over four-fifths of the eligible participants took soy food at least one day per week. The mixed effects model has shown the adjusted odds ratios (95% CI) of high-frequency consumers (4–7 days per week) were 0.46 (0.39–0.54) for depression with a cut-off score of 5, compared with non-consumers. Conclusions More frequent soy product consumption was associated with a lower risk of depression.